O processo de construção da imagem turística do Amazonas na percepção dos turistas internacionais - Anis Mary Freitas de Souza Pires (2004)
This research aims to find out how is the perseption of the foreigner tourist about the tourism in Amazonas, and how the state is seen abroad. The research is about the placement, communication and the image. We idetified the age, the country and the way of communication that influenced the tourist to visit Amazonas, besides the things that helped him to create this image. Trying to find out the relation between communication and image, and the way this image has been given out inother countries, through events, promotions and the way It is shown abroad. The conclusions reached by this research shows that there is a good point in showing the state´s natural beauty, but there is also a need of placing this image in a correct direction and create the correct image of the state. There is a necessity of creating competitives strategies to place the tourism of Amazonas.